Levantamento e caracterização dos poços subterrâneos na cidade de Pau dos Ferros - RN - Geraldo, Victor Lima (Universidade Federal Rural do Semi-Árido, 2019)
Due to periodic droughts the northeastern region of Brazil suffers from problems related to water scarcity, in this way, actions are needed to reduce the impacts caused by scarcity. Thus the use of groundwater is one of the solutions since the water from the aquifer is the source of this resource with quality and abundance. About 97% of the fresh water of the planet is in aquifers. The utility given to groundwater is varied, according to the Treat Brazil Institute (2019), in Brazil this water is used for agriculture, urban public water supply, domestic supply, industrial supply, among others. The present work had as objective to carry out the survey and characterize the underground sources of one of the supply sectors of the city of Pau dos Ferros / RN. The research was quantitative-descriptive and exploratory, where the private and public wells of the sector 02 of supply were visited, according to the sector division of Water and Sewage Company of Rio Grande do Norte (CAERN). The visit made it possible to characterize the underground sources in terms of physical aspects (depth, diameter, and location), consumption characteristics, quality standards and verification of the legalization of wells in management bodies (granting). Regarding the operation situation of the wells, of the 37 points visited, 49% are in operation, 14% are paralyzed or not installed and another 9% was not able to collect information about the situation. The results allowed to illustrate the reality of the studied sector defined quantitative and presenting percentages related to the ways of use of the wells in the city. It was possible to verify that the lack of registration of the underground sources, especially the private ones, is one of the problems present in the city under study, this can mean potential risks respecting the operating conditions and water quality of the wells analyzed.
Monografia
Keywords: Água subterrânea; Recursos hídricos; Escassez hídrica; Groundwater; Water resources; Water shortage; ENGENHARIAS::ENGENHARIA CIVIL